Assessment of Critical Reading Ability Using Indonesian Language Textbooks for the 2013 Curriculum and the Merdeka Curriculum - Akbariski, Habib Safillah; Harsiati, Titik; Basuki, Imam Agus (Universitas Negeri Malang, 2024)
Critical reading ability is a type of reading skill that involves critical thinking. There is a positive correlation between critical reading urgency and critical reading tests. In this regard, it is necessary to study the evaluations of the curriculums currently being implemented in Indonesia, specifically the 2013 and Merdeka curricula. This study is a type of qualitative descriptive research. The data of this study includes the level, stimulation level, and format of reading comprehension questions in the Indonesian textbook for the 10th grade 2017 version of the 2013 curriculum and the Indonesian textbook for the 10th grade 2021 version of the Merdeka curriculum. The data collection technique implemented in this study is the documentation or note-reading technique. Research results show that (1) there are six levels of awareness of critical reading skills in Indonesian textbooks for the 2013 class X and Merdeka programs. The six cognitive levels are interpretation, analysis, inference, evaluation, explanation, and self-regulation. The Indonesian Textbook 10th Grade, 2013 syllabus found 64 questions containing important reading content. Meanwhile, the Indonesian Textbook for the 10th grade of Merdeka Curriculum has 76 questions containing important reading content. Significant differences exist in the number of items measuring critical reading skills; (2) the question stimuli used included text, images-texts, and infographics; and (3) variations in question format including multiple-choice, true-false, brief, and descriptive answers.